SOCIO-ECONOMIC FACTORS AND LIVING STANDARDS OF THE POPULATION (International Conference on Economics, Finance, Banking and Management, 2025)
The growth of GDP per capita in the region is associated with the development of the manufacturing and non-manufacturing sectors in the region. The development of entrepreneurship can create a class of small owners, which is the main driving force of the market economy, create the opportunity to saturate the domestic market with consumer goods and services, and increase the income of each family.